Spatial interactions in local public debt. Evidence from Poland - Banaszewska, Monika (Economics and Business Review, 2023)
The aim of the paper is to investigate spatial interactions among the debt of 2,442 municipalities in Poland over the period 2005–2020. Using dynamic spatial Durbin model with two-way fixed effects it provides empirical evidence of positive spatial interactions. It is estimated that an increase in debt per capita in a given municipality by PLN 100 leads to an increase in the debt per capita in neighbouring municipalities by PLN 8–10. The result is robust to the various specifications of spatial weight matrix (contiguity vs. inverse-distance with a cut-off). It is also found that municipal debt in Poland suffers from high persistence over time.